Pengetahuan Masyarakat tentang Teh Kombucha sebagai Anti Kanker Kolon - Pustika Dewi, Restu Ayu Eka; Sudrajat, Agus (Indonesian Journal of Nutrition Science and Food, 2024)
Colorectal cancer is the third most common type of cancer, second only to lung and breast cancer, and the second leading cause of cancer death worldwide. Its growth and metastasis are closely related to the biosynthetic capacity of tumor cells, and colorectal cancer stem cells are at the top of the intratumoral hierarchy. Anti-colon cancer is currently still being developed by managing plants as medicine, one of which is with fermented drinks rich in antioxidants. Kombucha is a traditional health drink produced by fermenting sweet tea with a symbiotic culture of bacteria and yeast. The purpose of this study was to determine the description of public knowledge about kombucha tea as an anti-colon cancer. The study was conducted in the RT 05 RW 02 Lamper Krajan area, Lamper Lor Village, South Semarang District. The research sample that met the inclusion criteria was 54 respondents. The research method used quantitative descriptive with a purposive sampling technique design. study result showed that most respondents' knowledge about kombucha tea as an anti-colon cancer was still lacking, namely 35 people (64.8%). The importance of increasing knowledge about kombucha tea as an anti-colon cancer agent to prevent morbidity and mortality due to colon cancer.